Tinjauan tentang Keadaan Memaksa (Force Majeure) dalam Sengketa Perjanjian Murabahah di BNI Syariah Cabang Medan - Nisrina Mutiara Dewi (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2020)
Force marjeure is a condition that is likely to occur in a financing agreement in Islamic banking including murabahah contracts. This force majeure has elements that must be fulfilled which have been regulated in the KUHPer and Compilation of Sharia Economic Law. This type of research is a normative descriptive, type of normative legal research is research aimed at reviewing the Supreme Court's Decision Number 684 K / Ag / 2016. In a dispute the murabahah agreement reviews the force majeure in accordance with the applicable laws and regulations.